Drug Abuse In The Perspective of Understanding Students In Junior High School - Dosi Juliawati; Hengki Yandri; Rasmita Rasmita; Randi Saputra; Septya Suarja (Faculty of teaching training and education, 2023)
Drug abuse is a serious social problem in Indonesia. One of the factors that can influence the occurrence of drug abuse is the lack of understanding of students about the dangers of drugs. Therefore, this study explores students' understanding of drug abuse in junior high school. The research method used was quantitative, and the sample consisted of 100 junior high school students in Kerinci, which were taken using convenience sampling. The data were collected using a scale of students' understanding of drugs that had been tested for validity and reliability. The results showed that most students had a relatively good understanding of the dangers of drugs. However, there are still some students who do not understand the dangers of drugs, especially regarding the long-term impacts and legal consequences that can be obtained due to drug abuse. From the results of this study, it can be concluded that more intensive efforts are still needed to improve students' understanding of the dangers of drugs. Schools can develop more active and creative educational programs to improve students' understanding of the dangers of drugs and invite parents and the community to get involved in efforts to prevent drug abuse among adolescents. This conclusion can be used as a reference for developing programs and policies to combat drug abuse in Indonesia, especially among junior high school students.